TELAAH KONSEP KOMPETENSI SUMBER DAYA MANUSIA 5.0 BERBASIS SPIRITUALITAS DAN IMPLEMENTASINYA BAGI PERUSAHAAN - Lubis, Anggia Sari; Wulandari, Sari; Harahap, M Guffar (Bisnis-Net, 2024)
The purpose of writing this article is to examine the new conceptualization of human resource competence in the face of the era of Society 5.0.  The concept of human resource competence 5.0 based on spirituality is a new conceptualization generated based on a broad and in-depth literature review that is aligned with the need for human resource competence to be able toface the era of Society 5.0 which is characterized by the use of robots, Artificial Intelligence and the Internet of Things while maintaining the values of spirituality within. The concept of spirituality-based human resource competency 5.0 in  the previous study produced three dimensions on human resource competence 5.0 based on spirituality and can have a practical function for the business world, where human resource managers can implement the concept of spirituality-based  human resource competence 5.0 for The company is by better understanding the important dimensions for employees to  be able to adapt in the face of changes